2021
DOI: 10.3390/biomedicines9091184
|View full text |Cite
|
Sign up to set email alerts
|

Oral Antibiotic Prophylaxis Reduces Surgical Site Infection and Anastomotic Leakage in Patients Undergoing Colorectal Cancer Surgery

Abstract: Background: Surgical-site infection (SSI) and anastomotic leakage (AL) are major complications following surgical resection of colorectal carcinoma (CRC). The beneficial effect of prophylactic oral antibiotics (OABs) on AL in particular is inconsistent. We investigated the impact of OABs on AL rates and on SSI. Methods: A systematic review and meta-analysis of recent RCTs and cohort studies was performed including patients undergoing elective CRC surgery, receiving OABs with or without mechanical bowel prepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 61 publications
1
11
0
4
Order By: Relevance
“…Synbiotics are defined as mixtures of probiotics and prebiotics that confer a health benefit on the host by improving the survival and activity of beneficial microorganisms in the gut 33 . Previous systematic reviews and meta‐analyses focused on examine the effectiveness of probiotics and antibiotics separately, and these studies confirmed that probiotics and synbiotics used perioperatively decreased the incidence of SSI, 7‐9 and they also confirmed that preoperative administration of OAB was associated with lower incidence of SSI 1,2,4,6 . Our study was the first to compare probiotic treatments with OAB, and the results showed that pretreatment with OAB was a better option for reducing infection rate and anastomotic leakage rate.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Synbiotics are defined as mixtures of probiotics and prebiotics that confer a health benefit on the host by improving the survival and activity of beneficial microorganisms in the gut 33 . Previous systematic reviews and meta‐analyses focused on examine the effectiveness of probiotics and antibiotics separately, and these studies confirmed that probiotics and synbiotics used perioperatively decreased the incidence of SSI, 7‐9 and they also confirmed that preoperative administration of OAB was associated with lower incidence of SSI 1,2,4,6 . Our study was the first to compare probiotic treatments with OAB, and the results showed that pretreatment with OAB was a better option for reducing infection rate and anastomotic leakage rate.…”
Section: Discussionsupporting
confidence: 72%
“…Sepsis is still a lethal complication after abdominal surgery, although surgical techniques, and perioperative management have been prominently improved. Surgical site infection (SSI) is the most essential factor leading to sepsis, and SSI is prevalent in elective colorectal surgery, which occurs in 20% of the patients receiving colorectal surgery 1 . Prevention of SSI is therefore a job of the first order in postoperative management.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study revealed that the type of antibiotic was signi cantly associated with diarrhea after surgery treatment. Nowadays, the prophylactic use of antibiotics in abdominal surgery has been widely recognized, which can signi cantly reduce the incidence of surgical site infection and anastomotic leakage [26][27]. However, the abuse of antibiotics disrupts the symbiotic ecology of the intestinal tract, inhibits bene cial ora, and leads to a decrease in intestinal resistance to colonization and a continuous proliferation of pathogenic bacteria [28][29].…”
Section: Discussionmentioning
confidence: 99%